A Novel UCAN Power Control Algorithm Based on the Stackelberg Game - Huaping Chen; Zhiyu Wang; Zhongyang He; Guoqiang Li (IEEE Access)
With the wide application of underwater acoustic sensor network(UASN) in the Marine industry and commercial field, more and more experts have paid attention to it. However, the limited bandwidth and energy under water have led to a series of problems such as insufficient spectrum and power resources, which have brought great challenges to underwater acoustic communication. In this paper, A novel UnderWater Cognitive Acoustic Sensor Network(UCANs) power control algorithm based on the Stackelberg game is proposed to solve the problems of low system capacity, high inter-node interference, and poor communication quality due to unreasonable power allocation when Under Water Acoustic Sensor Networks (UASNs) share spectrum resources. Firstly, the primary and secondary users are regarded as the leader and follower in the Stackelberg game model, and the utility functions of the primary and secondary users are derived separately. Secondly, in the process of multiple games between the price adopted by the primary user and the transmit power set by the secondary user, the transmit power and unit power price of the secondary user are dynamically adjusted, and the two finally reach a Nash equilibrium state, so as to maximize the revenue of the whole network. Finally, The results of Aqua-Sim simulation platform show that the system capacity of the proposed algorithm is 27.9% higher than that of the traditional power control algorithm, at the same time, the algorithm improves the communication quality of the network while effectively controlling the transmit power of the subusers to reduce the interference between nodes.